The Concept of Drug-Resistant Epileptogenic Zone - Zhang, Chunbo; Kwan, Patrick (Frontiers in Neurology, 2019)
Resective surgery is the most effective way to treat drug-resistant epilepsy. Despite extensive pre-surgical evaluation, only 30-70% patients would become seizure-free after surgery. New approaches and strategies are needed to improve the outcome of epilepsy surgery. It is commonly observed in clinical practice that antiepileptic drugs (AEDs) could maintain seizure freedom in a large proportion of patients after surgery, who were uncontrolled before the operation. In some patients cessation of AEDs leads to seizure recurrence which, in most cases, can be controlled by resuming AEDs. These observations suggest that the surgery has converted the epilepsy from drug-resistant to drug-responsive, implying that the operation has removed the brain tissue accounting for pharmacoresistance, rather than the pathological substrate of epilepsy (at least not completely). Based on these observations, it is hypothesized that there is a drug-resistant epileptogenic zone (DREZ) which overlaps with the epileptogenic zone (EZ), and has both epileptogenic and drug-resistant properties. DREZ is necessary and sufficient to cause drug-resistant epilepsy, and its remove would render the epilepsy drug-responsive. Testing the hypothesis requires the development of new methods to define the DREZ, which may be used to guide surgical planning when the epileptogenic zone cannot be completely excised. This concept can also help understand the mechanisms of drug-resistant epilepsy, leading to new therapeutic strategies.